2023
DOI: 10.3390/foods13010047
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Plant Bioactive Compounds as Replacers of Synthetic Additives in the Food Industry

Gema Nieto,
Lorena Martínez-Zamora,
Rocío Peñalver
et al.

Abstract: According to the Codex Alimentarius, a food additive is any substance that is incorporated into a food solely for technological or organoleptic purposes during the production of that food. Food additives can be of synthetic or natural origin. Several scientific evidence (in vitro studies and epidemiological studies like the controversial Southampton study published in 2007) have pointed out that several synthetic additives may lead to health issues for consumers. In that sense, the actual consumer searches for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 186 publications
0
4
0
Order By: Relevance
“…Natural extracts have emerged as successful replacements for traditional additives due to the negative reputation of synthetic counterparts [ 17 , 18 ]. Research has demonstrated that natural extracts rich in polyphenols like chlorogenic acid, catechins, epicatechins, or hydroxytyrosol [ 19 , 20 , 21 ] can effectively substitute certain antioxidant additives, enhancing nutritional properties and providing health benefits to consumers [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Natural extracts have emerged as successful replacements for traditional additives due to the negative reputation of synthetic counterparts [ 17 , 18 ]. Research has demonstrated that natural extracts rich in polyphenols like chlorogenic acid, catechins, epicatechins, or hydroxytyrosol [ 19 , 20 , 21 ] can effectively substitute certain antioxidant additives, enhancing nutritional properties and providing health benefits to consumers [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…This extract appears notably more effective than other derivatives of Pistacia lentiscus L. compounds, emphasizing the need to refine our extraction techniques [ 9 ]. The integration of plant extracts into various sectors, including food, beverages, supplements, and cosmetics, has been a central focus of research, promising a comprehensive incorporation of nature’s gifts into our daily lives [ 10 ].…”
mentioning
confidence: 99%
“…Unfortunately, some of these products are proving difficult to dispose of, are not biodegradable or are toxic. As a result, there is an increasing emphasis on reducing the number of synthetic products or additives and replacing them with natural products or additives [1]. Through the use of physical, chemical and biochemical processes, these raw materials can be transformed into intermediates that can then be used to produce high-quality chemicals, polymers, lubricants, solvents or surfactants.…”
mentioning
confidence: 99%